Auto focus [videorecording (DVD)] - Schrader, Paul, 1946-; Kinnear, Greg, 1963-; Dafoe, Willem; Wilson, Rita; Fuller, Kurt, 1953-; Bello, Maria, 1967-; Leibman, Ron; Begley, Ed, Jr; Graysmith, Robert (Columbia TriStar Home Entertainment, 2003)
Bob Crane became well known as the star of the comedy hit series "Hogan's Heroes." With fame and success, Crane drove headfirst into the darker, destructive side of celebrity life. He eventually teamed with a video technician who helped him document his numerous sexploits. But when his fast living got out of control, the end result was a brutal murder that remains one of Hollywood's most scandalous unsolved mysteries.